Rancang Bangun E-Commerce Kopma Sale UNHAS Berbasis Web Untuk Kegiatan Kewirausahaan - Andi Muh. Ibnu Hibban Bagoes Malolo; Muhammad Fikri; Dhiyaa Unnisa; Riskawati Riskawati; Eliyah A M Sampetoding; A. Muh. Amil Siddik; Esther S Manapa (Puslitbang Sekawan Institute Nusa Tenggara, 2022)
UnhasCooperative UKM is a student activity unit engaged in the field of entrepreneurship. The entrepreneurial activity of Unhas Cooperative UKM students provides opportunities for students who have an interest in entrepreneurship to create business activities through analysis of market needs and opportunities. However, the entrepreneurship activities of the Unhas Cooperative UKM are still considered to be ineffective in their marketing system because the method used is still applying the conventional system, namely only through social media so that it has not been able to maximize its entrepreneurial potential. Departing from these problems, a web-based e-commerce was created entitled